Gastrointestinal stromal tumors of the colon and rectum - Roşulescu, Alexandra; Pechianu, Nicolae; Hortopan, Monica; Mihai, Mihaela; Dima, Simona; Stroescu, Cezar; Zamfir, Radu; Braşoveanu, Vladislav; Leonard, David; Vasilescu, Cătălin; Popescu, Irinel; Herlea, Vlad (Polish Journal of Pathology, 2020)
Gastrointestinal stromal tumors (GISTs) are rare neoplasms, colorectal location being met in less than 5% of cases. Knowledge about this site related particularities are limited. The aim of this study is to present our experience with colorectal GISTs between 2005 and 2018 from the clinical, morphological, and immunohistochemical perspectives, with emphasis on prognostic factors. From a total of 203 gastrointestinal stromal tumors registered, 12 were colorectal (6%). The number of colonic tumors surpassed that of the rectum (9 : 3) and on the right side were registered more cases than on the left side (6/3). 9 were primary tumors and 3 were recurrences. Men and women were represented equally and the age range was between 22 and 76. Tumor dimensions varied between 0.5 and 14 cm. Microscopically, spindle cell type was dominant. Mitotic rate was variable between 1 and 115/50HPFs. Accordingly, for primary tumors progression risks were assigned (low risk: 2 cases, intermediate risk: 3 cases and high risk: 4 cases). All GISTs were CD117 and DOG1 positive. Four of the patients died of the disease.